Innovations in cell culture-based influenza vaccine manufacturing - from static cultures to high cell density cultivations - Tilia Zinnecker; Udo Reichl; Yvonne Genzel (Taylor & Francis Group, 2024)
Influenza remains a serious global health concern, causing significant morbidity and mortality each year. Vaccination is crucial to mitigate its impact, but requires rapid and efficient manufacturing strategies to handle timing and supply. Traditionally relying on egg-based production, the field has witnessed a paradigm shift toward cell culture-based methods offering enhanced flexibility, scalability, and process safety. This review provides a concise overview of available cell substrates and technological advancements. We summarize crucial steps toward process intensification - from roller bottle production to dynamic cultures on carriers and from suspension cultures in batch mode to high cell density perfusion using various cell retention devices. Moreover, we compare single-use and conventional systems and address challenges including defective interfering particles. Taken together, we describe the current state-of-the-art in cell culture-based influenza virus production to sustainably meet vaccine demands, guarantee a timely supply, and keep up with the challenges of seasonal epidemics and global pandemics.